Rancang Bangun Purwarupa Sistem Kontrol Budidaya Tanaman Sawi Hijau Dengan Hidroponik Berbasis Arduino - Yaqin, Ainul; Fadillah, Nurul; Yuniarto, wendi; Hasan, Hasan (Electrical Network Systems and Sources, 2024)
Indonesian agriculture faces challenges in dealing with climate change and the increasingly limited availability of land, especially in urban areas. Hydroponics is a promising solution, especially for crops such as mustard greens that are sensitive to environmental changes, as they require relatively low temperatures. However, to ensure optimal growth, environmental controls such as water quality, pH, and temperature need to be well regulated. This research aims to improve and develop an automatic control system with Arduino as its platform. The system will monitor and control those parameters efficiently, allowing users to optimize the growth of hydroponic plants indoors. Thus, this project also provides a solution to the limited land in urban and tropical climates. This research uses Arduino Mega 2560 as the controller, DHT22 sensor to monitor the temperature, TDS sensor to determine the nutrient content of the solution, and pH sensor to determine the acid-base level of the solution. The result of this research is to facilitate efficient control of the hydroponic plant environment, increase productivity, and provide convenience in plant maintenance.